The effects of amino acid supplementation on muscular performance during resistance training overreaching - Ratamess, N. A.; Kraemer, W. J.; Volek, J. S.; Rubin, M. R.; Gomez, A. L.; French, D. N.; Sharman, M. J.; McGuigan, M. M.; Scheett, T.; Häkkinen, K.; Newton, R. U.; Dioguardi, F. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to examine the effects of amino acid supplementation on muscular strength, power, and high-intensity endurance during short-term resistance training overreaching. Seventeen resistance-trained men were randomly assigned to either an amino acid (AA) or placebo (P) group and underwent 4 weeks of total-body resistance training consisting of two 2-week phases of overreaching (phase 1: 3 × 8-12 repetitions maximum [RM], 8 exercises; phase 2: 5 × 3-5RM, 5 exercises). Muscle strength, power, and high-intensity endurance were determined before (T1) and at the end of each training week (T2-T5). One repetition maximum squat and bench press decreased at T2 in P (5.2 and 3.4 kg, respectively) but not in AA, and significant increases in 1RM squat and bench press were observed at T3-T5 in both groups. A decrease in the ballistic bench press peak power was observed at T3 in P but not AA. The fatigue index during the 20-repetition jump squat assessment did not change in the P group at T3 and T5 (fatigue index = 18.6 and 18.3%, respectively) whereas a trend for reduction was observed in the AA group (p = 0.06) at T3 (12.8%) but not T5 (15.2%; p = 0.12). These results indicate that the initial impact of high-volume resistance training overreaching reduces muscle strength and power, and it appears that these reductions are attenuated with amino acid supplementation. In addition, an initial high-volume, moderate-intensity phase of overreaching followed by a higher intensity, moderate-volume phase appears to be very effective for enhancing muscle strength in resistance-trained men.